2015
DOI: 10.18632/oncotarget.3233
|View full text |Cite
|
Sign up to set email alerts
|

TCGA data and patient-derived orthotopic xenografts highlight pancreatic cancer-associated angiogenesis

Abstract: Pancreatic ductal adenocarcinomas (PDACs) overexpress pro-angiogenic factors but are not viewed as vascular. Using data from The Cancer Genome Atlas we demonstrate that a subset of PDACs exhibits a strong pro-angiogenic signature that includes 37 genes, such as HDAC9, that are overexpressed in PDAC arising in KRC mice, which express mutated Kras and lack RB. Moreover, patient-derived orthotopic xenografts can exhibit tumor angiogenesis, whereas conditioned media (CM) from KRC-derived pancreatic cancer cells (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 73 publications
3
64
0
1
Order By: Relevance
“…S3C) and fibrotic (Supplementary Fig. S3E, arrows), and showed a high heterogeneity of vessel density as in human patients (22), with poorly vascularized regions (arrows in Supplementary Fig. S3D) and regions with a higher vessel density (arrowheads in Supplementary Fig.…”
Section: N6l Treatment Hampers Pdac Growth and Liver Metastasismentioning
confidence: 76%
“…S3C) and fibrotic (Supplementary Fig. S3E, arrows), and showed a high heterogeneity of vessel density as in human patients (22), with poorly vascularized regions (arrows in Supplementary Fig. S3D) and regions with a higher vessel density (arrowheads in Supplementary Fig.…”
Section: N6l Treatment Hampers Pdac Growth and Liver Metastasismentioning
confidence: 76%
“…Analysis of TCGA PDAC data was previously described [31, 32]. DESeq was performed for differential expression analysis [33], and genes were identified based on lymphangiogenesis gene ontology (GO) terms and recent reviews on tumor lymphangiogenesis [34, 35].…”
Section: Methodsmentioning
confidence: 99%
“…Arrays from KRC and KPC tumors was performed by Miltenyi Biotec as described [32]. Briefly, whole genome microarrays were hybridized with RNA from tumors or normal pancreata.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, targeting JAK1/2 can also inhibit counterregulatory suppressive mechanisms, such as MDSC function and tumor/stromal cell PDL1 expression (Delitto, et al, 2015b;Yu, et al, 2015). To complicate matters, the development of PC is associated with both activation of JAK receptors and suppression of negative feedback pathways in cancer cells, specifically the suppressor of cytokine signaling-1 (SOCS-1) (Craven, et al, 2016;Fukushima, et al, 2003;Gore, et al, 2015;Mace, et al, 2015;Nagathihalli, et al, 2015). These observations led to a phase II trial of JAK1/2 inhibition in metastatic PC, which demonstrated a therapeutic benefit in a subgroup of patients with elevated serum C-reactive protein levels (Hurwitz, et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%